A 2D discrete moisture diffusion model for simulating desiccation fracturing of soil. (May 2022) - Yan, Chengzeng; Luo, Zhiqiang; Zheng, Yucheng; Ke, Wenhui
Abstract: The desiccation fracturing of soil is widespread, which affects the migration of rainwater in the soil, and the stability of slopes or other projects. This paper proposes a simple two-dimensional (2D) discrete moisture diffusion model considering the influence of fractures on moisture migration. The moisture diffusion model is used in conjunction with the finite discrete element method (FDEM) to create a 2D discrete moisture diffusion-fracture coupling model, which is implemented in a GPU parallel multiphysics finite-discrete element software, namely MultiFracS. The coupled model is made up of three parts: a 2D discrete moisture diffusion model that takes into account the influence of fractures on moisture migration, a shrinkage deformation and stress computation, and an FDEM fracture mechanical computation. First, the moisture distribution in the system is analyzed using the moisture diffusion model. The shrinkage stress resulting from the moisture change is then computed. Finally, the shrinkage stress is added to the governing equation of FDEM to perform the fracture mechanical computation. Desiccation fracturing of the soil can be modeled using the processes outlined above. The paper firstly verifies the correctness of the 2D discrete moisture diffusion model to deal with the moisture migration in a continuous media, a media with impervious fractures or permeable fractures. Then, we give a principle that is used to determine the moisture exchange coefficient of the unbroken joint element through the parameter sensitivity analysis. Moreover, typical shrinkage deformation and stress problems and soil desiccation fracturing experiments are simulated. The simulation results are in good agreement with the analytical solutions and experiment results, verifying the effectiveness of the 2D discrete moisture diffusion-fracture coupling model to deal with shrinkage deformation and stress problems and the desiccation fracturing of soil. The coupled model provides a powerful solution tool to study the desiccation fracturing of soil.